Draft Five Year Plan 1978-83 Stationery and Printing Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
It is something unthinkable but in true that Printing and Stationery Department was given no plan funds for development of presses during the first and second five year plans, it found place for the first time under the third plan when Rs. 25/- lakhs were given for civil works and purchase of machines. From these funds building of Government Central press, Bhopal was constructed and a few printing machines most essentially needed were purchased. The press building at Bhopal was completed during the early part of the 4th plan. Due to paucity of funds even normal replacement of machinery could not be attended to, with the result that today, we have several machines which came from the merged states which are over sixty years old and which have outlived their utility and which are giving of poor production and in fact no production at all.
Government of Madhya Pradesh, Planning, Economics and Statistics Department